Leadership of the Head of Madrasah in Forming Santri Religious Competence in Madrasah Diniyah Takmiliyah - Karanto, Karanto; Aprilianto, Andika; Rofiq, Muhamamd Husnur (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2024)
Madrasah Diniyah Takmiliyah is one of the Islamic religious education institutions outside of formal education which is organized in a structured and tiered manner as a complement to the implementation of religious education. Madrasah Diniyah Takmiliyah Awaliyah Education is flexible, accommodating, and integrated, therefore its development can be carried out by the Central Ministry of Religion, education relates to the problem of madrasa principals in forming opportunities to hold meetings effectively with teachers in a conducive situation. This research uses a qualitative research approach in this study and aims to reveal existing data in the field by describing and interpreting something like what is in the field and linking cause and effect to something that happened during the research, to obtain a realistic picture of the program development process training. The research was conducted at the Al Munawaroh Laranganan MDTA, Lohbener Indramayu District. The results of the research show that the principal at MDTA Al-Munawaroh in Larangan village is still conventional in the pattern of forming the competence of his students. The principal in forming the competence of his students emphasizes only cognitive aspects. In the classroom, the teacher can provide teaching to students that emphasizes the effective domain (feelings and attitudes), without abandoning the values contained in the cognitive (rational thinking) and psychomotor (skills) domains.